2023
DOI: 10.1039/d3cy00651d
|View full text |Cite
|
Sign up to set email alerts
|

MIL-125(Ti)@ZIF-67-derived MIL-125(Ti)@TiO2 hollow nanodiscs decorated with Co3S4 for remarkable photocatalytic CO2 reduction

Abstract: Fabricating photocatalysts with customizable structure and composition using different metal-organic framework (MOF) building blocks has intriguing implications in chemistry and material science, but it is challenging to do so. Here,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…This light-driven photocatalytic CO 2 conversion not only helps to reduce the atmospheric concentration of CO 2 but also to acquire valuable fuels for energy production concurrently. 1,2 Historically, TiO 2 has intrigued researchers as a promising photocatalytic material for decades owing to its excellent material stability and favorable energy level alignment to CO 2 reduction and water oxidation since Inoue et al demonstrated TiO 2 photocatalysts for CO 2 conversion in 1979. 3 However, the 3.2 eV wide bandgap for anatase TiO 2 restricts its light absorption only to the UV region from the entire solar spectrum, and, thereby, the CO 2 conversion performance by TiO 2 photocatalysts remains at a low level.…”
Section: Introductionmentioning
confidence: 99%
“…This light-driven photocatalytic CO 2 conversion not only helps to reduce the atmospheric concentration of CO 2 but also to acquire valuable fuels for energy production concurrently. 1,2 Historically, TiO 2 has intrigued researchers as a promising photocatalytic material for decades owing to its excellent material stability and favorable energy level alignment to CO 2 reduction and water oxidation since Inoue et al demonstrated TiO 2 photocatalysts for CO 2 conversion in 1979. 3 However, the 3.2 eV wide bandgap for anatase TiO 2 restricts its light absorption only to the UV region from the entire solar spectrum, and, thereby, the CO 2 conversion performance by TiO 2 photocatalysts remains at a low level.…”
Section: Introductionmentioning
confidence: 99%